The Logic of Sense - Deleuze, Gilles 1925-1995; Lester, Mark (London Continuum, 2004)
Since its first publication, Logic of Sense has become a famous work of philosophical criticism, Working from Stoic philosophy to Lewis Carroll's literary and logical paradoxes and on to psychoanalysis, Deleuze seeks to determine the status of meaning and meaninglessness. Deleuze's exploration takes the reader through a series of inquiries with language, games, sexuality, schizophrenia and literature. Logic of Sense is one of Deleuze's seminal books not least in illuminating his most famous collaboration, with Felix Guattari, Anti-Oedipus.
Originally published in 1969
Keywords: 20th Century (1901-2000); Philosophy; France